Comparative assessment of knee extensor and flexor muscle strength measured using a hand-held vs. isokinetic dynamometer - Muff, Guillaume; Dufour, Stéphane; Meyer, Alain; Severac, François; Favret, Fabrice; Geny, Bernard; Lecocq, Jehan; Isner-Horobeti, Marie-Eve (Journal of physical therapy science, 2016)
[Purpose] To compare measurements of knee extensor and flexor muscle strength performed using a hand-held dynamometer and an isokinetic dynamometer in apparently healthy subjects. [Subjects and Methods] Thirty adult volunteers underwent knee muscle strength evaluation using an isokinetic or a hand-held dynamometer. [Results] Strong positive correlations were found between the 2 methods, with correlation coefficients r ranging from 0.72 (95% confidence interval [CI], 0.48-0.86) to 0.87 (95% CI, 0.75-0.94), depending on the muscle group and the isokinetic evaluation mode. The reproducibility of the hand-held dynamometer findings was good, judged by a coefficient of variation of 3.2-4.2%. However, the correlation between the 2 methods for the assessment of flexor/extensor ratios ranged from -0.04 to 0.46. [Conclusion] Knee extensor and flexor muscle strength recorded with a hand-held dynamometer is reproducible and significantly correlated with the isokinetic values, indicating that this method may in some cases be a useful replacement for isokinetic strength measurement. However, for strength ratio assessment, and when judged against the isokinetic standard, a hand-held dynamometer is not a valid option.